Competitive Pressure: Competitive Dynamics as Reactions to Multiple Rivals - Leon Zucchini; Tobias Kretschmer (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2011)
Competitive dynamics research has focused primarily on interactions between dyads of firms. Drawing on the awareness-motivation-capability framework and strategic group theory we extend this by proposing that firms' actions are influenced by perceived competitive pressure resulting from actions by several rivals. We predict that firms' action magnitude is influenced by the total number of rival actions accumulating in the market, and that this effect is moderated by strategic group membership. We test this using data on the German mobile telephony market and find them supported: the magnitude of firm's actions is influenced by a buildup of actions by multiple rivals, and firms react more strongly to strategically similar rivals.
urn:nbn:de:bvb:19-epub-12308-5
Keywords: 650; Wettbewerbsstrategie; Wettbewerb; Wettbewerbsstrategie; Mobilkommunikation; Deutschland